Recycling as a creative energy within the artwork formed with materials in Assemblage art - Kingdom Vision 2030 - Hilal, Faten Mahmoud Suleiman (Journal of Humanities & Social Sciences, 2024)
Research deals with recycling of raw material, that is, reuse and recycling, as it depends on re-processing of raw material that is dispensed, in a form that can be used again. He also touched on the plastic and intellectual concepts of creative artist towards material, as each artist had a different approach from other in terms of dealing with ready-made or waste materials, simple materials, and reused materials. He also touched on assemblage art, and one of its clear manifestations was the change in thought and formation in the direction of modern arts, as it became dependent on collecting multiple materials from different sources and working on their composition and harmony in the artwork. It also touched on creative artist and advantages of average individual problem was summed up in possibility of benefiting from recycling leftover raw materials, from which the artist derives his creative energy, relying on collage art in artwork formed with raw materials in light of Kingdom’s Vision 2030. The research also aims to implement an innovative artwork derived from creative energy generated from recycling leftovers of raw materials in field of molding with raw materials, and also to benefit from collage art in making designs for innovative artworks in light of Vision 2030. Theoretical side follows descriptive and analytical approach, and in the practical research applications, the experimental approach. One of results is that reuse or recycling of raw materials and materials can be useful in artwork formed with raw materials, and creative artist draws his creative energy from the field of raw materials recycling. Among the recommendations, the creative energy of the artist should be exploited in more than one artistic field and a different source, and work on the field of recycling and recycling of raw materials in the field of molding with raw materials from different points of view.